Voltammetry determination of selenium in various milk samples - Lian, Oo Kee (Universiti Sains Malaysia, 2015)
The interest concerning against selenium (Se) has been considerable arise in recent years as Se is an essential trace element for humans and it also exhibit toxicity effect in humans depending on its concentration. In this study, determination of the concentration of Se in various milk samples had been carried out using differential pulse cathodic stripping voltammetry (DPCSV) technique. This study provides a methodology that can be used to determine the concentration of selenium in various milk samples. Three types of raw fresh milks (goat’s milk, cow’s milk, and horse’s milk) and seven types of processed commercial milks had been analysed using DPCSV technique. These milk samples were undergone sample preparation procedure before being analysis. The milk samples were digested in HN03 : HCIO4 ( 1:1 ) mixture by a wet digestion procedure. All forms of Se in milk samples were converted into Se(IV) by the addition of HC1. The prepared samples were undergone dilution before proceed to analysis. The diluted milk samples were then added with electrolyte constitutes of 3.3g ammonium sulphate, O.lmol/L NaiEDTA dehydrate, and 100 ppm Cu standard solution before the analysis starts. The DPCSV of milk samples in HC1 solution showed a peak potential for selenium at -0.65V. The standard addition method was used to determine Se in the samples. The result for Se concentration in milk samples were successfully obtained in this study.